Pengelolaan Dan Pengembangan Zakat Di Indonesia - Ahmad Saepudin; Ahmad Damiri; Ahmad Ali Sopian; Faridha Rahyu (Jurnal Pelita Nusa, 2023)
Zakat given to mustahik will play a role as a supporter of their economic improvement if it is consumed for productive activities. The development of zakat is productive by using zakat funds as business capital, to empower the recipient's economy, and so that the poor can run or finance their lives consistently. With these zakat funds, the poor will get a steady income, increase their business, develop their business and they can set aside their income for saving. The purpose of this study is to determine the management and development of zakat in Indonesia. This research method uses library research with a qualitative descriptive analysis approach. The management of zakat by zakat amil has been exemplified since the time of the Prophet Muhammad, the management and distribution of zakat is carried out in an institutionalized and well structured manner. In the Indonesian context, this is reflected in the Law of the Republic of Indonesia Number 23 of 2011 concerning Management of Zakat, in which the Law regulates in sufficient detail the functions, roles and responsibilities of the Amil Zakat Agency (BAZ) and the Amil Zakat Institution. (LAZ). Furthermore, in order to maximize the role and function of zakat management institutions, of course, they must be managed as well as possible. It is not enough to end there, zakat management institutions must also be accountable, namely the trust given to the trust given by the muzakki and also the mandate in distributing it to mustahiq, in the sense of being right on target and effective.